An Analysis of Students’ Sustainability Awareness through Learning Using an ESD-Based E-Module: Analisis Kesadaran Berkelanjutan Siswa melalui Pembelajaran Menggunakan E-Modul Berbasis Education for Sustainable Development (ESD) - Andita Nur Sakinah Lili Budiarti; Andi Nurhidayah (UNIVERSITAS KHAIRUN, 2026)
This study aims to analyze students’ sustainability awareness after learning using an e-module integrated with Education for Sustainable Development (ESD) on the theme of traditional Indonesian fermented foods. The research employed a quantitative method using a questionnaire based on the Guttman scale, adapted from Gericke et al. (2018), consisting of 27 items covering three aspects: sustainability knowingness, sustainability attitudes, and sustainability behaviour. The data were analyzed using percentage calculations and N-Gain analysis. The results showed an increase in all aspects of students’ sustainability awareness, with improvements of 8.1% in knowledge, 5.9% in attitudes, and 18.4% in behaviour. However, the N-Gain results indicated that these improvements were still in the low category. This suggests that the use of ESD-based e-modules has not been significantly effective in enhancing students’ sustainability awareness within a short period. Therefore, continuous and sustained learning, along with the involvement of multiple stakeholders, is needed to optimize the development of students’ sustainability awareness.